ANALISIS NILAI TUKAR NELAYAN KABUPATEN SUMENEP TAHUN 2012 - Jakfar Sadik (Trunojoyo University of Madura, 2012)
The islands are quite large and long to be one of the strategic location for the development of marine-based economiy. There are several main reasons that make the region a high potential in the marine and fisheries sector: (1) has a huge marine resources both in terms of quantity and diversification, (2) have a high competitiveness in terms of raw materials and production owned generated, (3) industry in the marine and fisheries sector has linkages (backward and forward linkage) is strong with other industries, and (4) resource in the marine and fisheries sector is a readtly renewable resource (renewable resource) that persist in long term management of origin followed by the wise.Sumenep is one that is high fish producer in East Java, this is half of the area is Sumenep Islands Region, approximately 45,21% of the total area of the whole. So the research conducted to gain a vivid picture of domestic fishermen and fishing rate (NTN).Research shows of various types of transportation used by fishing boats jukong the screen, jukong engines, sailboats, boat engines, boat engines and aquaculture shows that the welfare of fishermen below the average index of 1 (one), which means that fishermen are able to meet the needs of primary but has not been able to meet the needs of secondary and tertiary. 6 types of transport are studied only fishermen fishermen fishing with this type of boat transport machinery, ship machinery and aquaculture are indices greater than one.